Financial abuse in domestic violence: a Shariah perspective - Adnan, Ieman Huda; Adnan, Ieman Sofiyya; Mohd Yusoff, Syarah Syahira; Hassan, Rusni (International Research Centre of Islamic Economics and Finance (IRCIEF-UIS), 2024)
This article examines financial abuse within domestic violence from the perspective of Maqasid Shariah, the higher objectives of Islamic law. While not explicitly mentioned, financial abuse contradicts core Islamic principles of fairness, justice, and protecting the well-being of family members. The analysis utilizes Quranic verses and Hadith narrations to explore financial responsibilities in marriage. It highlights the husband's obligation to provide for his wife and the importance of treating women with respect and kindness, including financial security. The article argues that financial abuse violates these principles and disrupts the balance within a family unit. It proposes using Maqasid Shariah as a framework to understand the ethical and legal dimensions of financial responsibility within marriage. This approach emphasizes the importance of preventing abuse and promoting a supportive family environment.